The effects of brand image, perceived trust and perceived risk on online booking intention: a conceptual model / Khairil Anuar Bahari ... [et al.] - Bahari, Khairil Anuar; Che Azmi, Muhammad Nuruddin; Mohd Kamal, Saiful Bahri; Zainol, Noorliza; Mahat, Fadhlina; Abdullah, Dahlan (Universiti Teknologi Mara Cawangan Pulau Pinang, 2020)
Over time, the use of the internet and technology has grown rapidly. Most businesses today use the internet as a means of communicating with their customers. This is because the internet has various interactive features and is always available for use. However, when there are too many interactive features to use, it can make the site more complex, less useful, and users find it difficult to use. Referring to an overview of past literature, the article generally proposes a conceptual framework with six propositions to understand the role of brand image, perceived trust and perceived risk of online buying intentions among hotel website users. As a basic theory, Stimulus Organizational Stimulation (SOR) has been used to support the proposed framework in this study. As a result, the researcher argues that brand image has an impact on the perceived risk and perceived trust of the hotel website. Consequently, hotel websites with higher perceived risk and perceived trust are more likely to influence online booking intentions.